LDL cholesterol: should guidelines include targets?. (March 2014) - Banerjee, Subhash; Kahali, Dhiman; Banerjee, Avantika; Brilakis, Emmanouil S
<x xml:space="preserve">Abstract</x> Elevated low-density lipoprotein cholesterol (LDL-C) is associated with adverse cardiovascular outcomes. The strategy of target-based LDL-C lowering to reduce the risk of coronary heart disease and secondary event rates is now well established. However, the strategy for treating to a target LDL-C, and whether there is a lower threshold level for LDL-C continues to be debated. We present, and critically analyze the evidence for a target-based LDL-C lowering strategy, and the safety and efficacy of intensive plasma LDL-C-lowering with traditional, and novel LDL-lowering therapies below current guideline targets.